Night Lights - Jim Hoy (Symphony in the Flint Hills, 2019)
Introduction: Among the many things plainsfolk, and other Americans as well, take for granted is good lighting. But many of you can probably, as I can, think back to the days before we had electricity and recall just why it was that we went to bed and got up with the chickens—there just wasn’t that much you could do by the light of a kerosene lamp.